The Brendan legend : texts and versions - Burgess, Glyn S. (Glyn Sheridan); Strijbosch, Clara, 1956- (Northern world ;, 2006)
"The Brendan Legend: Texts and Versions" deals with the vast textual tradition relating to the Irish Saint Brendan, known as 'The Navigator'. Stories about Brendan have been popular in the whole of Western Europe, from the seventh to the twentieth century. The themes of the book are the interrelated problems of the textual and literary embedding of Brendan texts. For the first time researchers in Celtic, German, Latin and Romance languages and literatures have co-operated on the Brendan tradition, and they have mapped the changes in textual traditions according to different circumstances and audiences. This book will be important to those studying the influence of Celtic literature on the European Continent, and, more generally, to those interested in the versatility of textual traditions over Western Europe